2016
DOI: 10.1101/cshperspect.a028100
|View full text |Cite
|
Sign up to set email alerts
|

Axonemal Dynein Arms

Abstract: Axonemal dyneins form the inner and outer rows of arms associated with the doublet microtubules of motile cilia. These enzymes convert the chemical energy released from adenosine triphosphate (ATP) hydrolysis into mechanical work by causing the doublets to slide with respect to each other. Dyneins form two major groups based on the number of heavy-chain motors within each complex. In addition, these enzymes contain other components that are required for assembly of the complete particles and/or for the regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
130
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(133 citation statements)
references
References 60 publications
2
130
0
1
Order By: Relevance
“…1 Among the wellcharacterized axonemal protein complexes, the outer and inner dynein arms (ODAs and IDAs, respectively) play a major role in the beating of both cilia and sperm flagella. 2 ODAs and IDAs are multiprotein ATPase complexes, which comprise heavy, intermediate, and light chains, and are attached to the A-microtubule of each peripheral doublet. 3,4 By anchoring to the B-microtubule of the adjacent doublet, ODAs and IDAs drive the sliding of the microtubule doublets and behave as indispensable molecular motors for the beating of those organelles.…”
mentioning
confidence: 99%
“…1 Among the wellcharacterized axonemal protein complexes, the outer and inner dynein arms (ODAs and IDAs, respectively) play a major role in the beating of both cilia and sperm flagella. 2 ODAs and IDAs are multiprotein ATPase complexes, which comprise heavy, intermediate, and light chains, and are attached to the A-microtubule of each peripheral doublet. 3,4 By anchoring to the B-microtubule of the adjacent doublet, ODAs and IDAs drive the sliding of the microtubule doublets and behave as indispensable molecular motors for the beating of those organelles.…”
mentioning
confidence: 99%
“…The mammalian ODA, a complex structure attached to the microtubules by a docking complex, is composed of multiple heavy, light, and intermediate dynein chains. 7,8 In a highly evolutionarily conserved fashion, the ODA structure repeats every 24 nm along the length of the axoneme and is controlled through the nexin dynein regulatory complex and radial spokes to produce a regular ciliary waveform. 9,10 Two types of human ODAs are described.…”
mentioning
confidence: 99%
“…The protein composition and role of the dynein arms were extensively studied in diverse model organisms. Within a single axonemal unit, there are four identical ODAs and seven IDAs (a single two-headed IDAf/I1 and six single headed IDAs a to e, and g) that differ in their protein composition and likely function [99]. The phenotypic analysis of the Chlamydomonas dynein arm mutants revealed that IDAs and ODAs perform different functions.…”
Section: Dynein Arm Subunitsmentioning
confidence: 99%